Rhythm Pattern Perception in Music: The Role of Harmonic Accents in Perception of Rhythmic Structure. - Dawe, Lloyd A. (My University, 1993)
The application of the label music to complex sound requires structure. Musical or rhythmic structure can be thought of as being due to the interaction of two theoretically distinct structures of phrase and metre. Perception of both metrical and phrase structure is dependent not only on the physical structure of the acoustic presentation but also upon cognitive structure being imposed on the auditory sensations. Early work in the psychology of music focused on establishing the perceptual cues that determine the parsing of music in time. These perceptual determinants can be categorized on the basis of the theoretical components of music: melody, harmony, rhythm, and timbre. With the exception of accent strength based on stability judgments of tones or chords (i.e., structural accenting), phenomenal accents have been assumed by some theorists to be equally-salient, additive, and categorical. The assumption of equal accent strength not only has been applied to different phenomenal accents within a theoretical component category but also between categories. Three series of experiments were conducted to test the assumption of equal weight and additivity of rhythmic cues. In the first series, a harmonic and a temporal accent were pitted against each other in such a way as to form different rhythm patterns. As well, two harmonic conditions which varied in the frequency of chord presentations (i.e., the compositerhythm) but not the frequency of chord changes (i.e., the harmonic-rhythm) were presented. Musicians and nonmusicians were requested to report perceived rhythm patterns in an attempt to determine the relative salience of the harmonic and temporal accents. In addition, a behavioural measure of the perceived metre was taken. Results indicated that the location of chord changes was the main determinant of subjects' rhythmic perceptions and the perceived onset of a measure. As well, although subjects primarily inferred different metres based on the composite-rhythm, an interaction of metrical and rhythmic choices was found indicating that perception of rhythm patterns and inference of metrical structure may not always be independent. In the second series of experiments, the contribution of harmonic-temporal and harmonic-structural features to the perception of rhythm patterns was investigated by pitting a harmonic and a temporal accent against each other in such a way as to form 5 possible rhythm patterns. Across the experiments, the chord progressions employed were varied, as was the timing of chord onsets (i.e., the composite-rhythm) and changes (i.e., the harmonic-rhythm). In all experiments, musicians and nonmusicians were requested to report perceived rhythm patterns in an attempt to determine the relative salience of the various accents. Results indicated that changes in the composite-and harmonic-rhythm led to a predictable change in an inferred metrical structure, and that all diatonic chord progressions lead to similar patterns of responses in which coincidences of harmonic, temporal, and inferred metrical accents were perceptually salient events. When a nondiatonic chord progression was employed however, there was neither evidence of an inferred metre, nor of responses on the basis of accent coincidence. Overall, musicians were found to primarily report rhythm patterns defined by the location of harmonic accents, while nonmusicians reported rhythm patterns defined by an inferred metrical structure. In the third series of experiments, the relative contribution of cues for metre inference was determined. In many theories of metre inference, the cues which serve as markers for major metrical accent locations are the basis from which one infers or determines a metre. However, phrase and metrical structure often support one another with phrase boundaries coinciding with metrically important locations. Thus, it becomes difficult to determine which cues, if any, are used exclusively, or predominantly as the basis for metre inference. Three experiments were conducted in which different time-spans defined by harmonic, melodic, and temporal accents, and their coincidences were systematically pitted against one another. Musicians and nonmusicians were requested to identify the metre of the stimuli as belonging to a category of either a triple (e.g., 6/8 or 3/4 time), or a duple metre (e.g., 2/4 or 4/4 time). It was found that musicians use harmonic information much more often and reliably than do nonmusicians who also use the temporal accent to define a metrical structure. Nevertheless, across the experiments, when a harmonic accent was present, subjects used that accent to define the metre. Furthermore, the coincidence of melodic accents was used more often than a temporal accent to determine a metrical structure. Together the three series of experiments highlight the significant role of harmonic accents in the perception of rhythm patterns in music.
Keywords: label music, complex sound, structure, musical or rhythmic structure, auditory sensations, psychology, harmony, accents, patterns